Oñati's youth facing the armed conflict: analysing the discourses of the first post-conflict generation - Velte, Samara (Oñati Socio-Legal Series, 2020)
This paper analises the discursive reconstruction of the Basque armed conflict in the oral narratives of the first post-conflict generation among Oñati's inhabitants, in order to observe how collective memory is being built and transmitted to the younger generations after the end of ETA's attacks. Using a discursive-historical approach and based on both in-depth and collective interviews, it focuses on three main aspects: how these adolescents categorise and evaluate events and actors of the violent past, the level of identification towards the events narrated, and the main canals through which both knowledge and attitudes are being transmitted. It concludes that adolescents perceive the conflict rather in its immaterial forms such as feelings and prejudices, and that they rely mostly on educational and familiar discourses when rebuilding the past. Some of the main voids identified are also signalised in this paper.